A review on the binder-free electrode fabrication for electrochemical energy storage devices. (July 2022) - How, Yu Yi; Numan, Arshid; Mustafa, Muhammad Norhaffis; Walvekar, Rashmi; Khalid, Mohammad; Mubarak, Nabisab Mujawar
Abstract: The rapid depletion of fossil fuels has catalysed the research on alternative renewable energy resources and energy storage devices. Electrochemical energy storage (EES) devices have gained popularity among energy storage devices due to their inherent features of long-life cycle, excellent energy and power densities, and the use of low-cost materials. The electrode in the EES device plays a major role in storing electrical energy, and the performance of such device mostly depends upon the selection of the electrodes. Different binder-free fabrication technologies for EES, such as chemical vapour deposition (CVD), electrochemical deposition (ECD), inkjet printing (IJP), spray pyrolysis (SP), sputtering deposition (SPT), layer-by-layer deposition (LbL), hydrothermal synthesis, vacuum filtration, sol-gel and electrospinning are critically reviewed in terms of the mechanism, operating procedure, operating condition, as well as the fabricated electrode's structure, morphology and performance based on recent literature. The advantages, limitations and suitability of deposition materials are also discussed and summarized for easy comparison. Highlights: Binder free electrode has a high potential to eliminates the dead volume. Different binder free fabrication technologies for EES are critically reviewed Fabricated electrode's structure, morphology and performance are reviewed Advantages, limitations and suitability of deposition materials are summarized for easy comparison.